Resource Recovery and Recycling in Sanitation is Key to Health, Water and Food Security. (2016) - Simha, Prithvi; Mathew, Melvin; Jain, Pulak; Ganesapillai, M.
Abstract: The present study argues that the issue of sanitation and the solutions to it extends far beyond its mere access; any envisioned improvement in sanitation technology must strive to rectify the shortcomings in centralized wastewater treatment wherein end-of-pipe technologies have been favored. It is evident that with the concurrent trends of projected population growth and urbanization, the provisioning of improved sanitation facilities will necessitate greater efforts and socio-technical innovations than those in place today. We thus illustrate that simultaneous provisioning of 'access' and 'improved sanitation' through urine diversion and resource recovery can help create multiple-win scenarios in developing countries especially in terms of health, food and water security. As a pathway for initiating circularity in flow of resources from sanitation to agriculture, we demonstrate a process that enables continuous recycling of nutrients (urea) following the source separation of urine from a urine diversion toilet. To do this, we look towards cyclical adsorption-desorption systems in a fixed-bed column packed with renewable agro-waste based activated carbon. The study places emphasis on the sorption optimization for which a Box-Behnken experimental design with Response Surface Methodology was applied. It was concluded that a column bed depth of 45.45 cm, urine flow rate of 2 L.h -1 and initial concentration of 20% allows 87.53% recovery of urea from human urine.